Ti13Nb14Zr1Cu medical titanium alloy, and preparation method and application thereof

CN122979704APending Publication Date: 2026-10-27SHANGHAI JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611275249.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该方案在力学性能与耐腐蚀性能方面具有一定优势,但体系中未引入抗菌功能元素,也未开展成骨及促血管生成功能的相关设计,无法满足骨植入材料对抗感染及血管化骨修复的综合应用需求

Benefits of technology

本发明通过Ti13Nb14Zr1Cu的合金成分体系设计,有效改善了纯钛及传统钛合金材料生物惰性较强、对成骨细胞分化及血管内皮细胞迁移缺乏有效调控的不足,在保证材料生物相容性的前提下,同时实现成骨促进、促血管生成及抗菌性能的协同优化,突破了现有钛合金体系多侧重于单一性能优化、难以兼顾多种生物功能的局限。合金中Nb与Zr元素可稳定β相结构,维持材料良好的生物相容性与力学适配性,适配骨植入的力学支撑需求;Cu元素以合金化形式均匀分布于钛基体中,既能够为材料提供稳定的抗菌功能来源,还可通过生理环境下的微量释放调节内皮细胞迁移行为,进一步协同提升材料的成骨分化促进效果,使单一材料体系同时具备多重生物功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979704A_ABST
    Figure CN122979704A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of medical implant metal materials, and particularly relates to a Ti13Nb14Zr1Cu medical titanium alloy and a preparation method and application thereof. The alloy is a beta type medical titanium alloy, and contains, in mass percentage, Nb 13%, Zr 14%, Cu 1%, and the balance of Ti. Nb and Zr are used for stabilizing the beta phase structure and ensuring biocompatibility, Cu is uniformly distributed in the form of alloying, and the material is endowed with antibacterial performance, and the osteogenesis and angiogenesis promoting ability are synergistically improved. The application is prepared by using an electron beam melting additive manufacturing process, and a three-period minimal surface G structure three-dimensional interconnected porous structure with a unit size of 1.5 mm and a porosity of 50% to 80% can be constructed, so that component regulation and integrated forming of the porous structure are realized. The alloy simultaneously has osteogenesis promoting, antibacterial and angiogenesis promoting performances, and the effect is better than that of pure titanium, and is suitable for medical implant fields such as bone defect repair and dental implantation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical implant metal materials technology, specifically relating to a Ti13Nb14Zr1Cu medical titanium alloy, its preparation method, and its application. Background Technology

[0002] Bone defect repair is one of the core treatment directions in orthopedic clinical practice. The number of bone defect cases caused by factors such as trauma, bone tumors, infection, and degenerative diseases is increasing year by year, and the clinical demand for high-performance bone implant materials continues to rise. Medical titanium and titanium alloys, with their excellent biocompatibility, corrosion resistance, and processing and forming properties, have become the most widely used metal implant materials in orthopedic implants, dental implants, and other fields. With the development of clinical medicine, the performance requirements for implant materials are no longer limited to basic biocompatibility and mechanical support functions, but are gradually developing towards a multi-functional synergistic direction, such as promoting osseointegration, reducing the risk of postoperative infection, and accelerating tissue vascularization repair.

[0003] Currently, widely used pure titanium materials are essentially bioinert, unable to effectively regulate osteoblast differentiation, vascular endothelial cell migration, and bacterial inhibition processes, thus failing to meet the application requirements for complex bone defect repair and long-term implantation. To improve the biofunctionality of titanium and titanium alloy implant materials, existing technologies primarily employ several optimization approaches: first, surface modification treatment, altering the material's surface morphology and physicochemical properties to enhance cell affinity; second, functional coating loading, constructing hydroxyapatite or bioactive ceramic coatings on the material surface to enhance osteogenic activity, or loading functional elements such as Ag, Cu, and Zn to impart antibacterial properties; third, porous structure construction, creating interconnected channels within the material to provide space for bone tissue ingrowth; and fourth, alloy composition design, introducing elements such as Nb and Zr into the titanium matrix to stabilize the β phase and reduce the elastic modulus, or introducing antibacterial functional elements to impart antibacterial capabilities.

[0004] Several technical solutions for optimizing the performance of medical titanium alloys have been disclosed. For example, Chinese patent application CN108456804A discloses a low-modulus copper-containing anti-infective medical titanium alloy. This alloy introduces Cu into a Ti-15Mo alloy system and combines this with a heat treatment process to precipitate Ti-Cu intermetallic compounds, giving the material both antibacterial properties and a low elastic modulus. However, the functional design of this solution mainly focuses on the matching of antibacterial properties and low modulus mechanical properties, without addressing the synergistic regulation of osteogenic and angiogenesis-promoting properties, thus failing to achieve a synergistic enhancement of multiple biological functions.

[0005] Chinese patent application CN105603255A discloses a method for 3D printing to prepare medical titanium alloy materials. It employs a multi-element composite design combined with laser 3D printing and heat treatment processes to improve material strength and reduce elastic modulus. This approach primarily focuses on optimizing the material's mechanical and forming properties; its elemental system design does not systematically and synergistically address biological functions such as osteogenic, antibacterial, and angiogenesis-promoting effects, thus exhibiting significant limitations in the biological functional dimension.

[0006] Chinese patent application CN109055814A discloses a Ti-Nb-Zr-Ag medical antibacterial titanium alloy. By introducing Ag, the material acquires antibacterial properties while simultaneously achieving a low elastic modulus and high compressive strength. While this approach improves upon the insufficient antibacterial properties of traditional titanium alloys, its functional design primarily focuses on the balance between antibacterial performance and mechanical properties, without addressing the synergistic enhancement of osteogenic differentiation and angiogenesis. Furthermore, the powder metallurgy sintering process makes it difficult to achieve the integrated construction of complex interconnected porous structures and material functional regulation, thus limiting its application in complex bone defect repair scenarios.

[0007] Chinese patent application CN118910468A discloses a medical-grade Ti-Ta-Nb-Zr alloy and its additive manufacturing method. By optimizing the content ratio of Ta, Nb, and Zr elements, the strength and corrosion resistance of the material are improved, while the elastic modulus is reduced. This approach has certain advantages in terms of mechanical properties and corrosion resistance, but it does not incorporate antibacterial functional elements, nor does it incorporate designs related to osteogenic and angiogenesis-promoting functions. Therefore, it cannot meet the comprehensive application requirements of bone implant materials for anti-infection and vascularized bone repair.

[0008] In summary, current medical titanium alloy technology still suffers from several technical shortcomings: First, insufficient synergy of biological functions. Existing titanium alloy systems often focus on optimizing single properties, with relatively limited design of the types and amounts of functional elements. This makes it difficult to simultaneously achieve synergistic optimization of osteogenic promotion, angiogenesis promotion, and antibacterial properties while ensuring good biocompatibility. Pure titanium and traditional titanium alloys are also highly bioinert, failing to effectively regulate osteoblast differentiation and vascular endothelial cell migration. Second, the integrated fabrication of structure and function is challenging. Traditional fabrication processes struggle to construct three-dimensional porous structures with controllable pore sizes and good connectivity while ensuring uniform alloy composition distribution, thus limiting the material's overall performance in cell adhesion, tissue ingrowth, and angiogenesis. Third, insufficient long-term stability of antibacterial function. Existing antibacterial titanium materials often rely on surface coatings or surface loading of single antibacterial elements, leading to issues such as coating peeling, insufficient persistence of antibacterial function, or difficulty in simultaneously achieving both antibacterial effect and cell compatibility.

[0009] Therefore, existing medical titanium and titanium alloy materials typically cannot simultaneously possess good mechanical support, osteogenic promotion, antibacterial properties, and angiogenesis-promoting capabilities. Furthermore, traditional preparation methods struggle to achieve integrated construction of alloy composition control and interconnected porous structures, limiting their effectiveness in bone defect repair and long-term implantation. Developing a multifunctional medical titanium alloy material that combines excellent mechanical properties, osteogenic activity, antibacterial properties, and angiogenesis-promoting capabilities is a pressing technical challenge in this field. Summary of the Invention

[0010] The purpose of this invention is to provide a Ti13Nb14Zr1Cu medical titanium alloy, its preparation method and application, which is suitable for various medical implantation scenarios such as bone defect repair implants and dental implants, and improves the overall effect and long-term safety of implantation treatment.

[0011] The objective of this invention is achieved through the following technical solution: This invention provides a Ti13Nb14Zr1Cu medical titanium alloy, which, by mass percentage, is composed of 13% Nb, 14% Zr, 1% Cu, and the balance Ti; the titanium alloy simultaneously possesses osteogenic promoting ability, antibacterial properties, and angiogenesis promoting ability.

[0012] Furthermore, the titanium alloy is a β-type medical titanium alloy; wherein Nb and Zr elements are used to stabilize the β-phase structure of the alloy and ensure the biocompatibility of the material, and Cu elements are uniformly distributed in the titanium matrix in an alloyed form to impart antibacterial properties to the material, and can promote endothelial cell migration and synergistically enhance osteogenic differentiation capacity through trace release under physiological conditions.

[0013] Furthermore, the titanium alloy has a three-dimensional interconnected porous structure. The porous structure uses the G structure in the three-period minimal surface structure as the basic structural unit, with a unit size of 1.5 mm and a porosity of 50% to 80%. The internal channels are in a three-dimensional interconnected state.

[0014] This invention also provides a method for preparing the Ti13Nb14Zr1Cu medical titanium alloy, characterized by employing an electron beam melting additive manufacturing process, specifically including the following steps: (1) Prepare alloy powder raw materials according to the target composition ratio of Ti13Nb14Zr1Cu; (2) The alloy powder is placed in the forming chamber of the electron beam melting equipment, and a preset three-dimensional structural model is imported. Layer-by-layer powder laying and electron beam scanning melting are performed in a vacuum environment. The Ti13Nb14Zr1Cu medical titanium alloy is obtained by layer-by-layer stacking.

[0015] Furthermore, the particle size range of the alloy powder in step (1) is 50 to 105 μm; before printing, the alloy powder is dried to ensure that the powder has good flowability and forming performance.

[0016] Furthermore, in step (2), the vacuum level inside the forming chamber is controlled to be 10. -3 ~10 -5 mbar; The process parameters for electron beam melting are: electron beam voltage 60-90kV, beam current 5-20mA, scanning speed 200-1000mm / s, and powder layer thickness 30-100μm.

[0017] Furthermore, the Y150plus electron beam melting equipment was used for preparation; the preset three-dimensional structural model mentioned in step (2) was constructed using Mathematica 12.0 software, and the three-period minimal surface G structure was used as the basic unit for the design of the porous structure.

[0018] Furthermore, the preparation method can achieve the integrated forming of a dense alloy structure and a porous structure.

[0019] The present invention also provides an application of the aforementioned Ti13Nb14Zr1Cu medical titanium alloy in the preparation of medical implant materials.

[0020] Furthermore, the medical implant material is a bone defect repair implant or a dental implant, which, after being implanted into the body, simultaneously exerts a synergistic effect of promoting osteogenic formation, resisting infection, and promoting angiogenesis.

[0021] The beneficial effects of this invention are as follows: This invention, through the design of a Ti13Nb14Zr1Cu alloy composition system, effectively improves upon the shortcomings of pure titanium and traditional titanium alloys, such as strong bioinertness and lack of effective regulation of osteoblast differentiation and vascular endothelial cell migration. While ensuring material biocompatibility, it simultaneously achieves synergistic optimization of osteogenic promotion, angiogenesis promotion, and antibacterial properties, overcoming the limitations of existing titanium alloy systems that often focus on optimizing a single property and struggle to accommodate multiple biological functions. In the alloy, Nb and Zr elements stabilize the β-phase structure, maintaining good biocompatibility and mechanical compatibility, meeting the mechanical support requirements of bone implantation. Cu elements are uniformly distributed in the titanium matrix in an alloyed form, providing a stable source of antibacterial function and regulating endothelial cell migration behavior through trace release under physiological conditions, further synergistically enhancing the osteogenic differentiation promotion effect of the material, enabling a single material system to possess multiple biological functions simultaneously.

[0022] This invention employs electron beam melting additive manufacturing to prepare titanium alloy materials. It can construct a three-dimensional porous structure with controllable pore size and connectivity while ensuring uniform distribution of alloy composition. This solves the problem of traditional manufacturing processes failing to achieve integrated construction of interconnected porous structures with controlled alloy composition. The constructed porous structure uses the G-structure, a three-period minimal surface structure, as its basic unit. It possesses excellent three-dimensional connectivity and a suitable porosity range, providing ample space for cell adhesion, spreading, and bone tissue ingrowth. Simultaneously, it provides structural support for endothelial cell migration and angiogenesis, effectively improving the material's overall performance in cell adhesion, tissue ingrowth, and angiogenesis, making it more suitable for repairing complex bone defects.

[0023] This invention introduces antibacterial functional elements through alloying, unlike existing antibacterial titanium materials that rely on surface coatings or single antibacterial elements. It effectively avoids problems such as coating peeling and insufficient antibacterial function persistence. The antibacterial function remains stable along with the matrix material over a long period, resulting in superior functional persistence and structural reliability. Simultaneously, the integrated additive manufacturing method eliminates the need for additional coating loading or subsequent structural processing, reducing the risk of interface failure. This allows the material to possess better structural stability and functional persistence in long-term implant applications, ensuring the long-term service effectiveness of the implant.

[0024] Compared with pure titanium materials, the Ti13Nb14Zr1Cu medical titanium alloy of the present invention has superior performance in osteogenic properties, angiogenesis promotion ability and antibacterial properties. It can more effectively promote osteogenic differentiation and mineralization of bone marrow mesenchymal stem cells, enhance endothelial cell migration ability, inhibit the growth of pathogenic bacteria and biofilm formation, and simultaneously meet the comprehensive needs of bone implant materials for bone integration, anti-infection and vascular repair. It is suitable for various medical implantation scenarios such as bone defect repair implants and dental implants, improving the overall effect and long-term safety of implantation treatment. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 The image shows the morphology of a Ti13Nb14Zr1Cu medical titanium alloy sample prepared by electron beam melting (EBM) technology in this invention. Figure 2 The elemental distribution and energy dispersive spectroscopy (EDS) composition analysis diagram of the Ti13Nb14Zr1Cu medical titanium alloy of this invention are shown. Figure 3This is a comparative evaluation diagram of the osteogenic properties of pure titanium materials and the Ti13Nb14Zr1Cu medical titanium alloy of this invention. Figure 4 A comparative graph showing the effects of pure titanium material extract and the Ti13Nb14Zr1Cu medical titanium alloy extract of the present invention on the migration ability of vascular endothelial cells. Figure 5 This is a comparative evaluation chart showing the antibacterial properties of pure titanium material and the Ti13Nb14Zr1Cu medical titanium alloy of this invention. Detailed Implementation

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0029] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0030] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0031] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0032] This invention provides a Ti13Nb14Zr1Cu medical titanium alloy, which is a β-type medical titanium alloy. By mass percentage, the alloy composition is: Nb 13%, Zr 14%, Cu 1%, with the balance being Ti. Nb and Zr elements are used to stabilize the β-phase structure of the alloy, ensuring good biocompatibility and mechanical properties. Cu elements are uniformly distributed in the matrix in an alloyed form, imparting antibacterial properties and regulating cell behavior through trace release under physiological conditions, thus exhibiting both osteogenic and angiogenic bioactivity.

[0033] Furthermore, the Ti13Nb14Zr1Cu medical titanium alloy can be fabricated into a three-dimensionally interconnected porous structure, suitable for implantation requirements in bone defect repair. The porous structure uses the G-structure from the three-period minimal surface structure as the basic unit, and three-dimensional modeling is completed using Mathematica 12.0 software. The unit size of the porous structure is 1.5 mm, with a porosity of 50%–80%, and the pores are fully three-dimensionally interconnected, providing spatial support for cell adhesion and spreading, bone tissue ingrowth, and angiogenesis.

[0034] The preparation method of Ti13Nb14Zr1Cu medical titanium alloy in this invention adopts electron beam melting (EBM) additive manufacturing process to achieve the integrated construction of uniform alloy composition distribution and porous structure, specifically including the following steps: Step 1: Pretreatment of powder raw materials Alloy powder with a particle size of 50-105μm was selected and prepared according to the target composition ratio of Ti13Nb14Zr1Cu. Before printing, the alloy powder was dried to remove the adsorbed moisture and ensure that the powder has good flowability and forming stability.

[0035] Step 2: EBM Additive Manufacturing The pretreated alloy powder is placed in the forming chamber of an EBM device (such as the Y150plus model), and the forming chamber is evacuated to a vacuum environment, with the vacuum level controlled at 10. -3 ~10 -5 mbar; Import a pre-built 3D structural model, perform layer-by-layer powder laying and electron beam scanning melting process, and obtain a titanium alloy component of the target shape by layer-by-layer deposition.

[0036] The EBM forming process parameters are as follows: electron beam voltage 60–90 kV, beam current 5–20 mA, scanning speed 200–1000 mm / s, and powder layer thickness 30–100 μm. By adjusting these parameters, integrated forming of dense and porous structures can be achieved, adapting to the structural requirements of different implantation sites.

[0037] The Ti13Nb14Zr1Cu medical titanium alloy described in this invention can be applied to orthopedic / dental medical implants such as bone defect repair implants and dental implants. Relying on the synergistic effect of osteogenic promotion, antibacterial and angiogenesis promotion, it can improve the bone integration efficiency, anti-infection ability and long-term use stability of implants.

[0038] Example 1: Preparation of a porous titanium alloy of Ti13Nb14Zr1Cu 1. Raw material preparation Accurately weigh each component according to the mass percentage: Nb 13wt%, Zr 14wt%, Cu 1wt%, with the balance being Ti, to prepare Ti13Nb14Zr1Cu alloy powder. The powder particle size is screened to be 50-105μm. The powder is dried in a vacuum drying environment at 120℃ to remove adsorbed moisture to ensure printing flowability, and then cooled to room temperature with the furnace before being discharged.

[0039] 2. Construction of porous model Mathematica 12.0 software was used for 3D modeling. The three-period minimal surface G structure was selected as the porous basic unit. The unit size was set to 1.5 mm and the porosity was 60%. The pores were ensured to be fully three-dimensionally connected. The model was output in STL format and then imported into the EBM device.

[0040] 3. EBM molding preparation Printing was performed using a Y150plus electron beam melting system, with the vacuum level in the forming chamber controlled at 5×10⁻⁶. -4 mbar; Set the forming process parameters: electron beam voltage 60kV, beam current 10mA, scanning speed 500mm / s, powder layer thickness 70μm. Complete the layer-by-layer powder laying, preheating and scanning melting according to the preset model, and finally obtain the Ti13Nb14Zr1Cu porous titanium alloy sample.

[0041] like Figure 1 As shown, the alloy sample prepared in this embodiment has a complete shape, a clear porous structure, and no obvious forming defects such as cracks or warping, and can accurately reproduce the designed three-dimensional porous morphology.

[0042] like Figure 2 As shown, energy dispersive spectroscopy (EDS) analysis of the sample revealed that Ti, Nb, Zr, and Cu were uniformly distributed in the matrix, and the mass content of each element was basically consistent with the designed composition, with no obvious elemental segregation.

[0043] Example 2: Verification of osteogenic properties of Ti13Nb14Zr1Cu alloy Rat bone marrow mesenchymal stem cells were harvested, and after adjusting the cell suspension concentration, they were inoculated onto the surfaces of Ti13Nb14Zr1Cu alloy samples and pure titanium control samples, and then cultured in a cell culture incubator. After 24 hours of culture, cell morphology was observed under a microscope, revealing that the alloy surface showed a greater number of adherent cells, more complete spreading, and more pronounced pseudopodia extension.

[0044] Extracts of the two materials were prepared and inoculated into bone marrow mesenchymal stem cells for culture. After 7 days of culture, alkaline phosphatase (ALP) activity was measured, and after 14 days of culture, Alizarin Red S (ARS) mineralization nodules were stained. Figure 3 As shown, compared with the pure titanium control group, the Ti13Nb14Zr1Cu alloy group showed stronger ALP staining positive signals, and the mineralized nodules stained with Alizarin Red S were larger and more numerous, indicating that the alloy can significantly promote osteogenic differentiation and mineralization of bone marrow mesenchymal stem cells.

[0045] Example 3: Verification of the angiogenesis-promoting properties of Ti13Nb14Zr1Cu alloy Human umbilical vein endothelial cells were harvested and cultured using Ti13Nb14Zr1Cu alloy extract and pure titanium extract, respectively. Scratch healing and Transwell migration assays were performed simultaneously.

[0046] In the scratch assay, after the cells had fused to a monolayer, a scratch treatment was performed. The culture medium containing the material extract was then replaced, and the cells were cultured for another 24 hours. The healing of the scratched areas was then observed. In the Transwell assay, cells were seeded in the upper chamber, and culture medium containing the extract was added to the lower chamber. After 12 hours of culture, the number of cells that had penetrated the membrane was counted.

[0047] like Figure 4 As shown, compared with the pure titanium control group, the Ti13Nb14Zr1Cu alloy extract group had a faster scratch healing rate and a greater number of transwell cells, qualitatively confirming that the alloy can effectively promote endothelial cell migration and has the biological potential to promote angiogenesis.

[0048] Example 4: Verification of the antibacterial properties of Ti13Nb14Zr1Cu alloy Staphylococcus aureus and Escherichia coli were selected as representatives of Gram-positive and Gram-negative bacteria, respectively. A suitable concentration of bacterial suspension was prepared and dropped onto the surface of Ti13Nb14Zr1Cu alloy sample and pure titanium control sample. After co-culturing for 24 hours, the samples were tested.

[0049] Colony counting was performed using the plate method, and bacterial survival status and biofilm formation were observed by live / dead fluorescent staining.

[0050] like Figure 5As shown, compared with the pure titanium control group, the number of bacterial colonies on the surface of Ti13Nb14Zr1Cu alloy was significantly reduced, and the formation of bacterial biofilm was significantly inhibited. The live / dead staining results showed that the proportion of dead bacteria on the alloy surface was higher, and the number of live bacteria was greatly reduced. Qualitatively, this indicates that the alloy has a good inhibitory effect on both pathogenic bacteria.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A Ti13Nb14Zr1Cu medical titanium alloy, characterized in that, The titanium alloy, by mass percentage, is composed of 13% Nb, 14% Zr, 1% Cu, and the balance Ti; the titanium alloy also possesses osteogenic promoting ability, antibacterial properties, and angiogenic promoting ability.

2. The Ti13Nb14Zr1Cu medical titanium alloy according to claim 1, characterized in that, The titanium alloy is a β-type medical titanium alloy; Nb and Zr elements are used to stabilize the β-phase structure of the alloy and ensure the biocompatibility of the material, while Cu elements are uniformly distributed in the titanium matrix in an alloyed form to impart antibacterial properties to the material and can promote endothelial cell migration and synergistically enhance osteogenic differentiation capacity through trace release under physiological conditions.

3. The Ti13Nb14Zr1Cu medical titanium alloy according to claim 1, characterized in that, The titanium alloy has a three-dimensional interconnected porous structure. The porous structure uses the G structure in the three-period minimal surface structure as the basic structural unit. The unit size is 1.5 mm, the porosity is 50% to 80%, and the internal channels are in a three-dimensional interconnected state.

4. A method for preparing the Ti13Nb14Zr1Cu medical titanium alloy according to any one of claims 1 to 3, characterized in that, The material is prepared using an electron beam melting additive manufacturing process, which specifically includes the following steps: (1) Prepare alloy powder raw materials according to the target composition ratio of Ti13Nb14Zr1Cu; (2) The alloy powder is placed in the forming chamber of the electron beam melting equipment, and a preset three-dimensional structural model is imported. Layer-by-layer powder laying and electron beam scanning melting are performed in a vacuum environment. The Ti13Nb14Zr1Cu medical titanium alloy is obtained by layer-by-layer stacking.

5. The preparation method according to claim 4, characterized in that, The particle size range of the alloy powder in step (1) is 50 to 105 μm; before printing, the alloy powder is dried to ensure that the powder has good flowability and forming performance.

6. The preparation method according to claim 4, characterized in that, In step (2), the vacuum level in the forming chamber is controlled to be 10. -3 ~10 -5 mbar; The process parameters for electron beam melting are: electron beam voltage 60-90kV, beam current 5-20mA, scanning speed 200-1000mm / s, and powder layer thickness 30-100μm.

7. The preparation method according to claim 4, characterized in that, The fabrication was carried out using a Y150plus electron beam melting device; the preset three-dimensional structural model mentioned in step (2) was constructed using Mathematica 12.0 software, and the porous structure was designed using a three-period minimal surface G structure as the basic unit.

8. The preparation method according to claim 4, characterized in that, The preparation method can achieve the integrated forming of dense and porous alloy structures.

9. The application of the Ti13Nb14Zr1Cu medical titanium alloy according to any one of claims 1 to 3 in the preparation of medical implant materials.

10. The application according to claim 9, characterized in that, The medical implant material is a bone defect repair implant or a dental implant, which, after being implanted into the body, exerts a synergistic effect of promoting osteogenic formation, resisting infection, and promoting angiogenesis.

Citation Information

Patent Citations

  • Medical titanium alloy material prepared by means of 3D (three-dimensional) printing

    CN105603255A

  • Low-modulus copper-containing anti-infective medical titanium alloy

    CN108456804A

  • Preparation method for medical antibacterial titanium alloy

    CN109055814A

  • Medical titanium alloy, medical titanium alloy additive and preparation method of medical titanium alloy additive

    CN118910468A